The Role of Brand Commitment in Mediating Brand Image and Brand Attacment to Repurchase Intention - Aziza, Aqualerra Dewi; Fikriah, Nur Laili (Institut Agama Islam Negeri Kendari, 2024)
This study aims to analyse the influence of brand image and brand attachment on repurchase intention with brand commitment as an intervening variable among Scarlett Whitening consumers who use Shopee in Malang City. The method used in this study was a quantitative approach with correlation analysis, with purposive sampling of 175 respondents from Generation Z and millennials and data analysis using Partial Least Square (PLS). The theories employed include the concept of brand image as the public's perception ofakan a brand, brand attachment as consumers' emotional connection to a brand, brand commitment reflecting psychological loyalty, and repurchase intention as consumers' intention to repurchase. The results indicate that brand image does not significantly influence brand commitment but has a positive direct effect on repurchase intention. Conversely, brand attachment has a significant positive effect on both brand commitment and repurchase intention. Brand commitment also has a significant positive effect on repurchase intention. It mediates the relationship between brand attachment and repurchase intention but does not mediate the relationship between brand image and repurchase intention. The practical implications of this study emphasise the importance of marketing strategies that focus on strengthening consumers' emotional attachment through personalisation and intensive interaction to increase loyalty and repurchase. This study is relevant for the Generation Z and millennial markets in Malang and the Shopee e-commerce distribution channel.